2009
DOI: 10.1117/12.818510
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a monocular helmet-mounted display on aircrew health: a 10-year prospective cohort study of Apache AH MK 1 pilots: study midpoint update

Abstract: A collaborative occupational health study has been undertaken by Headquarters Army Aviation, Middle Wallop, UK, and the U.S. Army Aeromedical Research Laboratory, Fort Rucker, Alabama, to determine if the use of the Integrated Helmet and Display Sighting System (IHADSS) monocular helmet-mounted display (HMD) in the Apache AH Mk 1 attack helicopter has any long-term (10-year) effect on visual performance. The test methodology consists primarily of a detailed questionnaire and an annual battery of vision tests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Firstly, earlier studies related to head-mounted displays have indicated subjective visual strain symptoms in users (Häkkinen et al, 2004;Hiatt et al, 2002: Mon-Williams et al 1993Howarth & Costello, 1997), although other studies have suggested that the symptoms are similar to those when using an ordinary display (Peli, 1998;Rushton et al, 1994;Sheedy & Bergström, 2002). Secondly, an HMD might occlude parts of the visual field and thus make the performance of the scanning task more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, earlier studies related to head-mounted displays have indicated subjective visual strain symptoms in users (Häkkinen et al, 2004;Hiatt et al, 2002: Mon-Williams et al 1993Howarth & Costello, 1997), although other studies have suggested that the symptoms are similar to those when using an ordinary display (Peli, 1998;Rushton et al, 1994;Sheedy & Bergström, 2002). Secondly, an HMD might occlude parts of the visual field and thus make the performance of the scanning task more difficult.…”
Section: Introductionmentioning
confidence: 99%